Studii sui Policheti del Golfo di Napoli. - La Greca, Marcello (Pubblicazioni della Stazione Zoologica di Napoli, 1946)
The A. has studied a collection of Polychaets [sic] from the Gulf of Naples, including two new species, (Protomystides bilineata n. and Oxydromus arenicolus n.) and a new variety (Glycera tesselata var. minor n.). Moreover two species (Nephtys cirrosa Ehl. and Proclea graffii Lang.) are described for the first time from the Mediterranean and three (Eurysyllis tuberculata EhI., Nereis kerguelensis McInt. and Eunice harassii Aud. & M. Edw.) are new to the Gulf of Naples.
World Polychaeta Database (WPolyDb)